Human Body Odour Composites Are Not Perceived More Positively than the Individual Samples - Fialová, Jitka; Sorokowska, Agnieszka; Roberts, S Craig; Kubicová, Lydie; Havlíček, Jan (i-Perception, 2018)
It is well established that composite facial images are perceived as more attractive compared with individual images, suggesting a preference for heterozygosity. Similarly, there is evidence that preferences for body odours might be linked to heterozygosity. Here, we tested whether blending individual body odours into composites would follow a similar pattern as observed in the perception of faces. We collected axillary odour samples from 38 individuals, which were subsequently assessed individually and as composites of two (N = 19) or four (N = 9) body odours regarding their pleasantness, attractiveness and intensity. We found no significant differences between mean ratings of individual odour samples or composites of two or four odour samples. Our results indicate that, in contrast to faces, composite body odours are not rated as more attractive. Composite body odours retain similar hedonic perceptual qualities as individual odours, thus highlighting differences in visual and chemosensory perceptual mechanisms.
Keywords: averageness; MHC; mate preferences; olfaction; heterozygosity; odour blend